Acute Exposure to the Cold Pressor Stress Impairs Working Memory Functions: An Electrophysiological Study - Xin, Zengyou; Gu, Simeng; Yi, Lei; Li, Hong; Wang, Fushun (Frontiers in Psychiatry, 2020)
The results of previous literature focusing on the effects of acute stress on human working memory (WM) are equivocal. The present study explored the effects of acute stress on human WM processing using event-related potential (ERP) techniques. Twenty-four healthy participants were submitted to stressful treatments and control treatment at different times. Cold pressor stress (CPS) was used as stressful treatment, while warm water was used as the control treatment before the WM task. Exposure to CPS was associated with a significant increase in blood pressure and salivary cortisol. After the 3-min resting period, systolic blood pressure (SBP) and diastolic blood pressure (DBP) for the CPS session significantly increased relative to the control treatment session (all p ≤ 0.01), and data also showed a significant increase of 20-min post-treatment cortisol concentration (p < 0.001) for CPS. Data from the CPS session showed significantly longer reaction times, lower accuracy, and WM capacity scores than that of the control treatment session. Interestingly, a difference between the two sessions was also found in N2pc and the late contralateral delay activity (late CDA) components. Specifically, although non-significant main effects of treatment were found for N2pc amplitudes, there was a significant interaction between treatments and stimuli conditions (processing load) [F(2,46) = 3.872, p = 0.028, η2 p = 0.14], which showed a pronounced trend toward equalization of N2pc amplitude across stimuli conditions during the CPS session clearly different from that of control treatment. As for amplitudes for late CDA, a nearly significant main effect of Treatment was found (p = 0.069). That is, the mean amplitude of the late CDA (−2.56 ± 0.27) for CPS treatment was slightly larger than that (−2.27 ± 0.22) for warm water treatment. To summarize, this study not only reported performance impairments in the WM task during CPS trials but also provided high temporal resolution evidence for the detrimental effects of acute stress on processes of information encoding and maintenance.